2020
DOI: 10.1175/jas-d-19-0044.1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Radiation in Accelerating Tropical Cyclogenesis in Idealized Simulations

Abstract: Recent numerical modeling studies indicate the importance of radiation in the transformation from a tropical disturbance to a tropical depression, a process known as tropical cyclogenesis. This paper employs a numerical modeling framework to examine the sensitivity to radiation in idealized simulations for different initial vortex strengths, and in doing so highlights when during tropical cyclogenesis radiation is most important. It is shown that all else being equal, a stronger initial vortex reduces the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 54 publications
5
13
0
1
Order By: Relevance
“…The leading contribution from longwave radiation to the increase of CIMSE within the circulation center at the early stage of simulations indicates that longwave radiation may be the primary factor in regulating TC genesis. This conclusion is consistent with previous modeling studies which suggested that longwave radiation is the leading contributor for tropical convective systems at their early stage (Carstens & Wing, 2020;Muller & Romps, 2018;Smith et al, 2020;Wing & Cronin, 2016;Wing & Emanuel, 2014…”
Section: Model Simulationssupporting
confidence: 93%
“…The leading contribution from longwave radiation to the increase of CIMSE within the circulation center at the early stage of simulations indicates that longwave radiation may be the primary factor in regulating TC genesis. This conclusion is consistent with previous modeling studies which suggested that longwave radiation is the leading contributor for tropical convective systems at their early stage (Carstens & Wing, 2020;Muller & Romps, 2018;Smith et al, 2020;Wing & Cronin, 2016;Wing & Emanuel, 2014…”
Section: Model Simulationssupporting
confidence: 93%
“…Since these two variables behave very differently in a warming climate-relative humidity staying near-constant while saturation deficit increases-a clear answer to this question would resolve a substantial uncertainty. Another area that shows a promising connection between genesis theories and global TC frequency is the growing body of work that shows that TC development is accelerated by cloud-radiative interactions in cloud-resolving simulations (Muller & Romps, 2018;Ruppert et al, 2020;Smith et al, 2020;Wing et al, 2016;Yang & Tan, 2020) and observations (Wu et al, 2021). Consistent with this, global TC frequency is reduced in GCM simulations with realistic boundary conditions when these radiative interactions are suppressed (B.…”
Section: Scaling Up Genesis Theoriesmentioning
confidence: 91%
“…The large amount of water vapor and clouds in the disturbance region traps the upwelling infrared radiation from the surface and the lower atmosphere, resulting in a horizontal radiative warming anomaly beneath (e.g., Bu et al., 2014; Fovell et al., 2016; Gray & Jacobson, 1977; Tao et al., 1996). This radiative warming anomaly induces a secondary circulation between the disturbance and the outer environment, which is believed to be very favorable for tropical cyclogenesis (e.g., Muller & Romps, 2018; Nicholls, 2015; Ruppert et al., 2020; Smith et al., 2020). Ruppert et al.…”
Section: Introductionmentioning
confidence: 99%
“…(2020) speculated that the intensification of the secondary circulation forced by the radiative warming anomaly might transport more moisture and low‐level angular momentum into the disturbance region, which directly promotes TC development. Besides, the intensification of the upward branch of the secondary circulation and the increase of moisture import are also favorable for convection in the disturbance region, accelerating tropical cyclogenesis as well (e.g., Nicholls, 2015; Ruppert et al., 2020; Smith et al., 2020). The relative roles of water vapor and clouds in the acceleration of radiation feedback on TC genesis are unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation